Tortura e ditadura: uma comparação entre os filmes Prá frente, Brasil (1982) E o que é isso,companheiro? (1997) - Ciffoni, Flavio Bandeira (2015)
This study compares profiles of torture during the period of Brazilian military dictatorship, with the help of two films on this theme, Prá frente, Brasil (Onward Brazil) (1982), by Roberto Farias, and O que é isso, companheiro? (Four Days in September) (1997), by Bruno Barreto. With this aim, it adopts the methodology proposed by author Manuela Penafria (2009) and, thus, it outlines and analyses the representations of torture in these selected films. Thus, the study has identified specific sequences for the film analysis and description in each of the motion picture productions. It justifies these choices by the dramatic link between action and torture scenes, in addition to the portrayals of guiding elements for the descriptions and analyses, such as the presence of the tortured and torturers, with further addition of situations related to the issue of torture in Brazilian dictatorship. This work presents historical aspects such a regime, primarily the years from 1968 to 1973, periods corresponding to the narratives of either film, based upon the theoretical contributions from authors such as Élio Gaspari (2002a, 2002b, 2003), Marcelo Ridenti (1993), Jacob Gorender (1987), Daniel Aarão Reis Filho (2000) and Beatriz Kushnir (2001). In the first comparative stage, the reflection falls upon the creation, functioning and role of Embrafilme, in particular the actions of director Roberto Farias while he headed this statutory board, and, later, upon the repercussions from the sanctions by censorship units taken against his film Prá frente, Brasil (1982). In the second stage, regarding the film from Bruno Barreto, the survey presents a time frame pertaining to the occasion of the hijacking of the American Ambassador, in 1969, with the resulting conclusion of that action. In particular, the study comments upon a panorama of the publication, marketing and repercussion of the book O que é isso, companheiro? (1979) by Fernando Gabeira, since it served as guide for the script for this film. In addition, the research highlights the changes in finance modes and their consequences during the moment known as Cinema da Retomada (Resuming Cinema), according to authors Lúcia Nagib (2002, 2007), Pedro Butcher (2005) and Luiz Zanin Oricchio (2003). In summary, these productions, by reason of distinct options by their directors, failed to identify or name those guilty of torture practices incurred during the period of Brazil's dictatorial military regime, yet nevertheless they contributed to the collective imaginary and still allow new reflections to be made upon this theme and that era that have not been explored sufficiently and more pointedly.